Gene expression changes in human cerebral arteries following hemoglobin exposure: implications for vascular responses in SAH - Shafeeque, Chathathayil M.; Harmanci, Arif O.; Thomas, Sithara; Dienel, Ari C.; McBride, Devin W.; Peeyush, Kumar T.; Blackburn, Spiros L. (Frontiers in Physiology, 2025)
Subarachnoid hemorrhage (SAH), characterized by the presence of hemoglobin (Hb) in the subarachnoid space, significantly impacts cerebral vessels, leading to various pathological outcomes. The toxicity of cell-free Hb released from erythrocytes and its metabolites after SAH causes vasoconstriction and neuronal damage, and correlates with delayed ischemic neurological deficits (DIND). While animal models have provided substantial and invaluable data in the research of aneurysmal SAH, the specific effects of subarachnoid blood on cerebral arteries remain greatly understudied. Here, we describe the changes in the genetic profile of human cerebral arteries exposed to free Hb for 48 h. We performed an ex vivo exposure, followed by mRNA sequencing of the vessels. Compared to controls 54 genes were downregulated, and 53 genes were upregulated in human cerebral arteries after Hb exposure. Enrichment analysis identified the ferroptosis pathway as the most significantly affected. Further lipid peroxidation (LPO) assays and elevated ACSL4 gene expression support a ferroptosis pathway. Additionally, Hb exposure altered key signaling pathways essential for vascular stability (PI3K-Akt, MAPK), modified G-protein signaling mediated by RGS1/2, and suppressed key transcription factors such as KLF5, NR4A1, and FOS. Our results underscore the critical role of Hb in driving pathological responses in brain vessels. Furthermore, our dataset could be valuable for developing interventions after SAH and may help identify the underlying causes of vascular injury.